1987
DOI: 10.1037/0096-1523.13.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Infants' detection of visual-tactual discrepancies: Asymmetries that indicate a directive role of visual information.

Abstract: Infants' cross-modal functioning was investigated in two studies. In Study 1, 11-month-old infants were confronted with five different visual-tactual discrepancies created with a mirror arrangement. The infants' behavioral reactions to the discrepancies were compared with their behavior on matched control trials with a forced-choice judgement procedure. Infants detected discrepancies in which they saw an egg and felt a cube, saw a fur-covered cube and felt an egg, and saw a cross and felt a fur-covered cube. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
4
18
1
Order By: Relevance
“…This supports and extends the findings of Westman, Westman, and Orellana (1996) s and is consistent with the finding that infants use visual guidance for their manual exploration (Bushnell & Weinberger, 1987). The clarity of the sensory impressions from vision, sound, smell, and internal sensations increased with the age at which the event occurred.…”
Section: Discussionsupporting
confidence: 92%
“…This supports and extends the findings of Westman, Westman, and Orellana (1996) s and is consistent with the finding that infants use visual guidance for their manual exploration (Bushnell & Weinberger, 1987). The clarity of the sensory impressions from vision, sound, smell, and internal sensations increased with the age at which the event occurred.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, success on the test trial could depend on the extent to which the characteristics primed during familiarization are useful for distinguishing between the test choices. If this is so, it should be possible to manipulate the direction of crossmodal asymmetries by manipulating characteristics that differentiate the paired test stimuli (see Bushnell & Weinberger, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one study has assessed the role of specific manual exploratory behavior in cross-modal performance. Bushnell and Weinberger (1987) did so in a study of 11-month-olds' detection of visual-tactual discrepancies. Unlike the studies discussed so far, where information must first be gathered in one modality and then used in another, in Bushnell's paradigm objects are presented simultaneously to vision and touch and discrepancies are created with a mirror arrangement.…”
mentioning
confidence: 80%
“…However, Brown and Gottfried (1986) reported that 1-, 3-, and 5-month-olds provided no evidence for haptically discriminating any of four different pairs of shapes, and both Streri (1987) and Streri and Pecheux (1986) reported certain failures for intermodal transfer of the shape information they studied; interestingly, these failures were in opposite directions for 2-3-month-olds (no vision to touch transfer) and 5-month-olds (no touch to vision transfer). Bushnell and Weinberger (1987) likewise found cross-modal asymmetries for both shape and texture information even on the part of infants as old as 11 months. Based on these results, they suggested that infants' haptic exploration is not as effective on its own as when it is "directed" by visual information.…”
Section: Introductionmentioning
confidence: 65%